Myocardial infarction in the young woman due to spontaneous coronary artery dissection - D. N. Brylyakova; E. V. Stepanova; D. D. Zubarev; E. V. Mineeva; G. A. Kukharchik (Российский кардиологический журнал, 2021)
.